Makna Kata “Dipotong” (ekkópto) Dalam Roma 11:22 - Tjong, Andrew Lucas; Binar, Sri (Jurnal Teologi dan Pelayanan Kerusso, 2025)
The struggle over whether salvation can be lost or not is a topic that frequently attracts attention among Christians. In the view that salvation can be lost, one of the verses used is Romans 11:22, particularly the word "cut off." On the other hand, there are views that disagree with interpreting this verse as evidence of the possibility of losing salvation. Based on these differing views, a deeper examination of the referenced verse is necessary. In analyzing this verse, the author will use a hermeneutical method with four analytical approaches: contextual, grammatical, lexical, and historical analysis. Based on the exploration of the text in Romans 11:22, it was found that the meaning of the word "cut off" does not refer to the possibility of losing salvation but serves as a stern warning that those who have been saved should not fall back into sin and transgression, as happened to the people of Israel in the past. However, if believers fall into sin, God will take firm action to remind them to repent and return to Him.